Influência de atividades de modelagem na qualidade dos argumentos de estudantes de Química do ensino médio - Paula Cristina Cardoso Mendonca (2011)
The importance of argumentation for science education, and the relationships between modelling and argumentation are emphasised by the literature. When I was a teacher at the medium level, I could realise that modelling favoured argumentation and, at the same time, was influenced by it. As a consequence, in this research we aim at investigating, from specific instruments: (i) the quality of the arguments produced by medium level students when they participate into modelling activities based on the Model of Modelling diagram for the teaching of two chemical topics: ionic bonding, and intermolecular interactions; (ii) the relationships between their arguments and the steps of the modelling process; and (iii) how modelling influenced the students argumentation. Data were collected in a second year medium level class from a public school. The teacher had already had some experiences in conducting investigative activities. All the modelling activities were discussed with her. The students had not previous experience with investigative activities. Data gathering occurred between February and June 2009. All the lessons were video-recorded with the focus in three students groups, the researcher produced field notes, and the written activities produced by the students were photocopied. All the videos were transcribed, and by merging all data we produced case studies for each of the topics for two of the groups. The definition of scientific curricular argument was proposed. This definition and the students arguments from a pilot study based the elaboration of an instrument for analysing the level of the arguments. In the case studies, the classification of the level of the arguments took into account their plausibility into the context in which they were produced. In the case studies, we describe how students dealt with anomalous data for their models, and how the teacher conducted the discussions. We probed whether there were relationships between the use of primary or secondary data and the level of the arguments. We also identified some students attitudes as doing the lesson or doing the school and doing science in order to discuss possible relationships between the level of the arguments and the students attitudes during the lessons. The analysis of the case studies based the discussion of the research questions. The definition of scientific curricular argument as well as its use form the instrument for analysing the level of the arguments showed to be coherent because it made it possible to analyse the arguments during the modelling process. Our data show that the modelling-based teaching activities (mainly those related to steps 3 (test of the model) and 4 (evaluation of the model) of the diagram) are adequate to favour the production of students models close to the curricular ones, the production of arguments, and the expression of high quality arguments. During the activities of the teaching of intermolecular interaction, students produced more high quality arguments than during the activities of the ionic bonding teaching. This may be a consequence of their participation into the initial activities, due to the knowledge and reasoning skills they developed in such a situation. The teachers role in conducting the activities, mainly the refutation to the models that were incoherent to the curricular models, was essential in favouring the students argumentation. We realised that it was not only the nature of data that favoured their use in the arguments, but also the context in which they were analysed and their complexity. The use of anomalous data in a teaching context that involved the collaboration in the construction of knowledge and that was guided by the teacher was important for supporting key changes into the students models. The students attitudes, as well as the use of concrete materials and gestures influenced the production of their arguments. The students conceptual knowledge influenced the improving of the quality of their arguments, and vice-versa. We suggest the use of the Model of Modelling diagram to base the elaboration of teaching activities that aim at favouring the argumentation in other contexts, and the use of the instrument for the analysis of the level of the scientific curricular arguments in other research that investigate such arguments into knowledge construction processes